2016
DOI: 10.3390/en9020118
|View full text |Cite
|
Sign up to set email alerts
|

Structural Reliability of Plain Bearings for Wave Energy Converter Applications

Abstract: Abstract:The levelized cost of energy (LCOE) from wave energy converters (WECs) needs to be decreased in order to be able to become competitive with other renewable electricity sources. Probabilistic reliability methods can be used to optimize the structure of WECs. Optimization is often performed for critical structural components, like welded details, bolts or bearings. This paper considers reliability studies with a focus on plain bearings available from stock for the Wavestar device, which exists at the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In the present project, it is very useful to compare the use of ANOVA in [3,4], to improve the proposed method of analysis. Through optimizing other variables such as those mentioned in [5,6] it is possible to generate substantial improvements that will be taken into account in future work in the optimization of manufacturing processes. It can be concluded that DEA model is a method that can be of great help, and although it will not replace the DOE, if it allows manufacturing companies to perform analysis and process improvements in a faster way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present project, it is very useful to compare the use of ANOVA in [3,4], to improve the proposed method of analysis. Through optimizing other variables such as those mentioned in [5,6] it is possible to generate substantial improvements that will be taken into account in future work in the optimization of manufacturing processes. It can be concluded that DEA model is a method that can be of great help, and although it will not replace the DOE, if it allows manufacturing companies to perform analysis and process improvements in a faster way.…”
Section: Discussionmentioning
confidence: 99%
“…In [4], developed the DOE, improved manufacturing tolerances in permanent magnet motors. Taking into consideration [5], applied the DOE in a spot welding process to identify the key parameters of the process, which influence the tensile strength of welded joints. Also, DOE had been employed successfully en R&R analysis [6], surface response analysis [7] and, algorithm analysis [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Wavestar WEC is described as a point absorber (Marquis et al, 2012;Ambühl et al, 2016;Heo and Koo, 2021), oscillating body system or wave activated system (Chen et al, 2018;Curto et al, 2021), or attenuator (Amrutha and Sanil Kumar, 2022). It is essentially a group of floats whose operation does not depend on the direction of the waves, ascending and descending with the upward and downward motion of the waves.…”
Section: Figurementioning
confidence: 99%